Результаты исследований по разработке способов изготовления шлифпорошков из синтетических алмазов однородного зернового состава с повышенными абразивными свойствами и прочностью - Новиков, Н.В.; Богатырева, Г.П.; Никитин, Ю.И.; Петасюк, Г.А.; Полторацкий, В.Г. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The methods and technological scheme of production of special grinding powders (AC6 and
AC15) of demand grit sizes are presented in this article. These powders possess high strength and
high abrasive properties in combination with high content of main fraction as well as high uniformity of grit composition. Optimal operating regimes for non-standard equipment have been are chosen, sieves with narrow module (m = 1.189) have been applied. According to suggested technology
the initial product to produce grinding powders is concentrated product of diamond synthesis as
well as composite compacts from undersize particles including ultradispersed diamond (UDD). The
diamond grinding powders produced according to this technological scheme are recommended to
produce numerous nomenclature of grinding and polishing tools including single-layer tools.